Circadian Plasticity in the Brain of Insects and Rodents - Krzeptowski, Wojciech; Hess, Grzegorz; Pyza, Elżbieta (Frontiers in Neural Circuits, 2018)
In both vertebrate and invertebrate brains, neurons, glial cells and synapses are plastic, which means that the physiology and structure of these components are modified in response to internal and external stimuli during development and in mature brains. The term plasticity has been introduced in the last century to describe experience-dependent changes in synapse strength and number. These changes result from local functional and morphological synapse modifications; however, these modifications also occur more commonly in pre- and postsynaptic neurons. As a result, neuron morphology and neuronal networks are constantly modified during the life of animals and humans in response to different stimuli. Nevertheless, it has been discovered in flies and mammals that the number of synapses and size and shape of neurons also oscillate during the day. In most cases, these rhythms are circadian since they are generated by endogenous circadian clocks; however, some rhythmic changes in neuron morphology and synapse number and structure are controlled directly by environmental cues or by both external cues and circadian clocks. When the circadian clock is involved in generating cyclic changes in the nervous system, this type of plasticity is called circadian plasticity. It seems to be important in processing sensory information, in learning and in memory. Disruption of the clock may affect major brain functions.